Childhood and Sexuality Contemporary Issues and Debates - Moore, Allison (Studies in Childhood and Youth, 2018)
This book explores how children engage with sex and sexuality. Building on a conceptual and legal grounding in sexuality studies and the new sociology of childhood, the authors debate the age of consent, teenage pregnany, sexual diversity, sexualisation, sex education and sexual literacy, paedophilia, and sex in the digital age. Whilst Moore and Reynolds recognise the necessity of child protection and safeguarding in the context of risk, danger and harm, they also argue that where these stifle children's sexual knowledge, understanding, expression and experience, they contribute to a climate of fear, ignorance and bad experiences or harms. What is necessary is to balance safeguarding with enabling, and encourage judicious understandings that advance from a rigid developmental model to one that recognises pleasure and excitement in children's nascent sexual lives. Exploring that balance through their chosen issues, they seek to encourage changed thinking in professional, personal and academic contexts, and speculate that children might teach adults something about the way they think about sex. Childhood and Sexuality will be of interest to students, scholars and professionals across a range of subjects and disciplines including sociology, social work, criminology, and youth studies.